Multidimensional signal processing of NMR data - Lin, Zhiping (2008)
Although significant progress has been achieved in sequencing the human genome in recent years, the molecular basis for many diseases can only be understood if the three-dimensional (3D) structures of the proteins encoded by genes are available. Sequencing a gene is nowadays essentially a routine task, whereas the determination of a 3D structure of a protein is still a major task that will typically take years to complete. Currently, nuclear magnetic resonance (NMR) spectroscopy is still one of the two major methods for the determination of 3D protein structures as other methods are still not very accurate The processing and analysis of multidimensional (nD) NMR data is an important step in NMR spectroscopy. There are several methods for processing nD NMR data, but they are mainly based on the one-dimensional (1D) techniques. Moreover, there does not exist any rigorous measure for assessing how good the existing methods for estimating the NMR parameters. In this project, we analyze and process nD NMR data using nD system theory and signal processing techniques and global optimization methods. An important step in our investigation is to interprete nD NMR data as the impulse response of a separable nD state space system.